Studi Pengolahan Tepung Biji Mangga Menggunakan Metode Perebusan Dan Suhu Pengeringan Yang Berbeda - Khusnul Khotimah (Jurusan Pertanian Politeknik Pertanian Negeri Samarinda Kampus Sei Keledang Jalan Samratulangi, Kotak Pos 192 Samarinda 75123, 2017)
The objective of this research was to study the utilization of mango seed to produce flour that serves multiple purposes. The study used various boiling time and drying temperature to produce mango seed flour with different qualities. The results indicate that treatment A1B1 produced the best mango seed flour based on the yield and organoleptic tests (15 minutes boiling time and 40oC drying temperature). A1B1 showed yield of 13.54%, water content of 6.72%, ash content of 2.57%, and color test of 3.02%